2002
DOI: 10.1136/jcp.55.6.461
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutation in breast cancer. Correlation with cell kinetics and cell of origin

Abstract: Aim: Several studies have investigated the expression of the cytokeratins (CKs), vimentin, the epithelial growth factor receptor (EGFR), the oestrogen receptor (ER), and the progesterone receptor (PgR), in breast cancer, but no study has directly compared p53 mutations with these phenotypic and differentiation markers in the same case. The present study was designed to provide some of this information. Methods: The expression of the p53 and bcl-2 proteins was evaluated by immunohistochemistry in relation to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
(28 reference statements)
2
27
0
Order By: Relevance
“…These findings can be explained by the postulate that subsets of breast cancer exist that are either derived from different normal cell populations or differentiate along different pathways as a consequence of having different alterations in the control mechanisms of cell proliferation and hence neoplastic progression; this may be p53-dependent in the tumours with a less differentiated, basal phenotype and p53-independent in those tumours with a more differentiated, pure luminal form. The existence of p53 mutations by chance in the later subset cannot, however, be excluded, 29,30 as shown by our finding that occasional tumours in groups 1, 2, 3 and 6 exhibited p53 expression. This supports the suggestion that cell type-specific genetic pathways are maintained in distinct genetic evolutionary pathways in mammary carcinogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…These findings can be explained by the postulate that subsets of breast cancer exist that are either derived from different normal cell populations or differentiate along different pathways as a consequence of having different alterations in the control mechanisms of cell proliferation and hence neoplastic progression; this may be p53-dependent in the tumours with a less differentiated, basal phenotype and p53-independent in those tumours with a more differentiated, pure luminal form. The existence of p53 mutations by chance in the later subset cannot, however, be excluded, 29,30 as shown by our finding that occasional tumours in groups 1, 2, 3 and 6 exhibited p53 expression. This supports the suggestion that cell type-specific genetic pathways are maintained in distinct genetic evolutionary pathways in mammary carcinogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…Defective MMR system is a very frequent genetic alteration in many malignancies, including squamous cell carcinoma, and recent studies have demonstrated these alterations in potentially malignant disorders, such as AC [33,35]. In addition, changes in system MMR genes can cause disorders in cell cycle proteins such as p53 [22]. Based on this, we performed the immunohistochemical analysis of cell cycle proteins p53 and p21 in the same sample used in our previous study [33] to verify if there is any relationship between the alterations in hMSH2 expression and the aforementioned cell cycle proteins in different stages of lip carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Several studies have proposed close interactions among p53, Bcl-2 and hMSh2 proteins during carcinogenesis. 3,7,9,11 This proposition is supported by two notions. First, p53 can inhibit Bcl-2 protein expression through p53-regulatory domain in the Bcl-2 gene.…”
Section: Introductionmentioning
confidence: 76%
“…34 Several studies reported that there is a relationship between MMR genes, oncogenes and TSGs during mammary carcinogenesis. 3,7,9,11 Interestingly, the concomitant expression of p53 and hMSH2 was seen in 11 cases. This finding suggests that p53; hMSH2 protein expression is regulated by a common mechanism.…”
Section: Expression Of Bcl-2 Protein In the Normal Breast Bpbd Dcismentioning
confidence: 99%
See 1 more Smart Citation